Eesti kunstnikud = Artists of Estonia 2. - Bernstein, Boris; Helme, Sirje; Juske, Ants; Kurvitz, Raoul; Laanemets, Mari; Liivrand, Harry; Saar, Johannes; Treier, Heie; Varblane, Reet (Tallinn : Center for Contemporary Arts, 2000)
Allik, Peeter ; Arro, Jaak ; Karmin, Mati ; Kask, Eve ; Kelpman, Rein ; Kurismaa, Mari ; Leis, Malle ; Lestberg, Ly ; Lill, Ado ; Mikof, Mare ; Mäetamm, Marko ; Nukke, Mall ; Ole, Kaido ; Palm, Jüri ; Pere, Peeter ; Põder, Anu ; Poldroos, Enn ; Pääsuke, Tiit ; Rajangu, Raul ; Siib, Liina ; Tali, Andres ; Ulas, Peeter ; Viik, Urmas ; Vinogradov, Valeri ; Vint, Toomas
biog., bibliog. p. 241-291
Engels
Ests
boek
Keywords: Estland